2013
DOI: 10.4103/0973-1482.113386
|View full text |Cite
|
Sign up to set email alerts
|

Post-radiotherapy locoregional recurrence of hyalinizing clear cell carcinoma of palate

Abstract: Clear cell carcinoma of the salivary glands is a rare tumor that represents less than 1% of all salivary tumors and is a new disease that is only recognized in recent years. It is rare and the standard treatment is still under investigation. This tumor often follows an indolent course and treatment includes wide surgical excision with or without adjuvant radiotherapy. Recurrence of the hyalinizing clear cell carcinoma (HCCC) after complete surgical resection is uncommonly documented. We hereby report a case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…Neck dissection, where specified, was usually unilateral, and limited to supraomohyoid levels I to III. Adjuvant or neoadjuvant therapy was performed in 26 cases, including 8 patients who had also undergone lymph node dissection . Radiation was the preferred adjuvant modality in 24 cases, with combined chemotherapy/radiotherapy being administered in 2 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Post-operative radiotherapy is recommended when a total surgical removal of the primary tumor is not attainable [13]. However, Gon et al [2] reported a case of locoregional recurrence after 6 years, despite all surgical margins being free of neoplasms and administration of three cycles of adjuvant radiotherapy, suggesting that the therapeutic value of radiotherapy for HCCC may be limited.…”
Section: Discussionmentioning
confidence: 97%
“…Hyalinizing clear cell carcinoma (HCCC) was first described by Milchgrub et al as a rare carcinoma of the minor salivary glands [1], representing less than 1% of all salivary tumors [2]. The tumor is characterized by low-grade morphology with only occasional metastatic spread that can achieve good overall treatment outcome [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation